Determination of 17beta-estradiol in dosage formulations: gel and patch (Revista Brasileira de Ciências Farmacêuticas, 2005)
A visible spectrophotometry method was developed for quantification of 17beta-estradiol in gel and in patch, tranformations by using diazotised sulfanilamide as the colorimetric reagent. The azo-compound formed showed a maximum absorption in 480 nm, and the reaction was linear in a concentration range from 10,0 to 28,0 µg/mL. When applied to dosage formulations it showed to be precise and accurate.